2010
DOI: 10.1104/pp.110.158857
|View full text |Cite
|
Sign up to set email alerts
|

SHORT-ROOT and SCARECROW Regulate Leaf Growth in Arabidopsis by Stimulating S-Phase Progression of the Cell Cycle

Abstract: SHORT-ROOT (SHR) and SCARECROW (SCR) are required for stem cell maintenance in the Arabidopsis (Arabidopsis thaliana) root meristem, ensuring its indeterminate growth. Mutation of SHR and SCR genes results in disorganization of the quiescent center and loss of stem cell activity, resulting in the cessation of root growth. This paper reports on the role of SHR and SCR in the development of leaves, which, in contrast to the root, have a determinate growth pattern and lack a persistent stem cell niche. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 81 publications
7
92
0
Order By: Relevance
“…To distinguish between these possibilities, we next measured cytokinin content in shr and wild-type plants. As shown in Table II, the concentrations of several types of cytokinin were significantly higher in both root and shoot of shr, consistent with the expression of SHR in both organs Dhondt et al, 2010;Gardiner et al, 2011). This result, along with the observations that exogenous cytokinin causes shr-like vascular patterning, strongly suggests that high cytokinin concentration is a major cause of the vascular patterning defect in shr.…”
Section: Shr Controls Cytokinin Homeostasissupporting
confidence: 71%
“…To distinguish between these possibilities, we next measured cytokinin content in shr and wild-type plants. As shown in Table II, the concentrations of several types of cytokinin were significantly higher in both root and shoot of shr, consistent with the expression of SHR in both organs Dhondt et al, 2010;Gardiner et al, 2011). This result, along with the observations that exogenous cytokinin causes shr-like vascular patterning, strongly suggests that high cytokinin concentration is a major cause of the vascular patterning defect in shr.…”
Section: Shr Controls Cytokinin Homeostasissupporting
confidence: 71%
“…Figure 2 shows that OsSHR2 transcripts accumulate in developing veins of plastochron P2 to P4 rice leaf primordia (where a plastochron is the time interval between the initiation of leaf primordia, and P1 is the youngest and closest to the shoot meristem from which the leaves are derived). In contrast to Arabidopsis, where AtSHR transcripts accumulate in procambium and persist throughout vascular development (Dhondt et al, 2010;Gardiner et al, 2011;Cui et al, 2014), OsSHR2 transcripts are detectable only in veins after the surrounding bundle sheath cells have differentiated, and then expression is relatively short-lived (Fig. 2C).…”
Section: Duplicate Shr Genes In Grassesmentioning
confidence: 98%
“…In contrast, the ABI4 transcript level in the shr mutant remained almost unchanged, and the ABI5 transcript level was only moderately increased. Because SCR and SHR are also expressed in the shoot apical meristem, leaf primordium, and young leaves Dhondt et al, 2010;Gardiner et al, 2010) and shr and scr leaves showed obvious differences in sugar hypersensitivity, we also analyzed these ABI genes in the shoot. A similar trend was observed for ABI4 and ABI5 (Supplemental Fig.…”
Section: Sugar Levels Are Elevated In Scrmentioning
confidence: 99%